Advanced MIS and Digital Transformation for Increased Creativity and Innovation in Business - Ekren, Gülay (IGI Global, 2019)
As businesses undergo digital transformation, technologies will lead to greater efficiencies and change how we interact in traditional relationships among suppliers, producers, and customers, as well as between human and machine. One such technology is the introduction of management information systems (MIS) that provide a company with the coordination, control, analysis, and visualization of information by collecting from various digital environments. In today's digital age, information needs to be managed, and MIS have the ability to transfer the information obtained by computer systems to t.